Generation of Kcnma1fl‐tdTomato, a conditional deletion of the BK channel α subunit in mouse. Issue 11 (4th November 2015) - Zemen, Betsir G.; Lai, Michael H.; Whitt, Joshua P.; Khan, Zulqarnain; Zhao, Guiling; Meredith, Andrea L.
Abstract: BK large conductance calcium‐activated K + channels (KC a 1.1) are expressed widely across many tissues, contributing to systemic regulation of cardiovascular, neurological, and other specialized physiological functions. The pore‐forming α subunit is encoded by the Kcnma1 gene, originally named mSlo1 in mouse and slowpoke in Drosophila . Global deletion in mouse ( Kcnma1 −/− ) produces a plethora of defects in neuron and muscle excitability, as well as other phenotypes related to channel function in nonexcitable cells. While homozygous null mice are viable, the ubiquitous loss of BK function has complicated the interpretation of phenotypes involving the interaction of multiple cell types which independently express BK channels. Here, we report the generation of a targeted allele for conditional inactivation of Kcnma1 using the Cre‐loxP system ( Kcnma1 fl ‐tdTomato ). Cre‐mediated recombination generates a null allele, and BK currents were not detectable in neurons and muscle cells from Nestin‐Cre; Kcnma1 fl/fl and SM22 α ‐Cre; Kcnma1 fl/fl mice, respectively. tdTomato expression was detected in Cre‐expressing tissues, but not in Cre‐negative controls. These data demonstrate the utility of Kcnma1 fl ‐tdTomato for conditional deletion of the BK channel, facilitating the understanding of tissue‐specific contributions to physiological function in vivo. Abstract : BK large conductance calcium‐activated K + channels (KC a 1.1) are expressed widely across many tissues, contributing to systemic regulation of cardiovascular, neurological, and other specialized physiological functions. We generated a targeted allele for conditional inactivation of Kcnma1 using the Cre‐loxP system ( Kcnma1 fl ‐tdTomato ). Cre‐mediated recombination inactivates BK channel expression and activates expression of a tdTomato reporter, facilitating the understanding of tissue‐specific contributions of BK channels to physiological function in vivo.